WW II behind closed doors [videorecording (DVD)] : Stalin, the Nazis and the West - Rees, Laurence, 1957-; Rees, Laurence, 1957-; Rees, Laurence, 1957-; Williams, Andrew; Gunton, Bob; Petrenko, Alekseĭ, 1938-2017; Humpoletz, Paul (2/entertain : BBC Video ; Distributed in the USA and Canada by Warner Home Video, 2009)
Joseph Stalin - the supreme leader of the Soviet Union - was a tyrant responsible for the death of millions. He also had some unlikely relationships during the Second World War. This ambitious series uses exclusive evidence gained from the actual conversations and secret meetings Stalin conducted. Dramatic reconstructions carefully sourced from archive material, reveal how the great leaders decided the future shape of the post-war world. These decisions had immediate and often harrowing effects for those on the ground. Their story is told through documentary footage, dramatic reconstructions and illuminating interviews.